A Fifth Amendment Sword: The Inconsistent Doctrine of Privilege Withdrawal and The Burden Placed on Civil Plaintiffs in Police Misconduct Suits - Rudy Rosenmayer (Washington University Journal of Law and Policy, 2025)
In civil litigation, the doctrine of withdrawal affords defendants the ability to assert their Fifth Amendment privilege protecting against self-incrimination and then revoke the privilege after the suit has progressed. Such shifting use of the privilege generates several challenges for a plaintiff’s case, turning the Fifth Amendment into a defense strategy. This ploy is ripe for abuse in police misconduct suits. Civil plaintiffs face several, specific obstacles in such suits relating to a late withdrawal of the privilege by defendant police officers. But allowing a late privilege withdrawal can create an incentive structure, vulnerable to pressure by a municipality, to tactically extend the privilege—resulting in officers sitting out discovery but not being appropriately sanctioned for doing so. Circuit courts have approached this Fifth Amendment withdrawal doctrine in inconsistent manners. The result has, at times, meant that certain plaintiffs in police misconduct suits fail to have a fair process during their civil trial. This note analyzes three particular circuit court approaches and abuse of the doctrine. Through this analysis, this note concludes that the doctrine of withdrawal needs a consistent application to mitigate incentives for abuse. It will then propose such remedies to address obstacles created by the withdrawal doctrine including creating harmony across circuits in late withdrawal and direct action by Congress or the Supreme Court.
Keywords: FifthAmendmentAbuse; CivilLitigationReform; PoliceMisconductTrials